An Epidemiological Study on Hand Washing Practices Among Health Care Workers in Hospitals of Mangalore City - Harsha Kumar H N; Devi Dileep (Medsci Publications, 2013)
Introduction: There is very little published information on hand washing practices of Health Care Workers (HCWs), their knowledge, perceived barriers & facilities for practicing hand washing in hospitals from India. So this study was undertaken. Such studies give important inputs for further research, policy & planning. Materials & Methods: This cross-sectional study conducted in hospitals of mangalore city had two components: 1) Direct observation of hand washing pre & post patient contact followed by 2) administration of anonymous questionnaire testing knowledge. A total of 142 hand washing opportunities were studied. The study was conducted in consenting hosptials affiliated to medical schools, nursing homes, corporate hospitals. Two study tools based on used were: 1) Proforma to record practices; and 2) Questionnaire to test knowledge of HCWs. Results: Only 129 observations could be made. Though the HCWs had general awareness about Hand Washing Practices (HWPs), they lacked information about specific aspects & the practices were poor. Low hand washing rates (%) were observed among nurses (28) & doctors (23).There was gap between knowledge and practice. Knowledge of doctors on various aspects of hand washing was inadequate though it was better than nurses. "High Work Load" & "Lack of Time" were perceived to be important barriers for HWPs. Shortage of sinks was noticed in hospitals. Conclusion: There is a need to evolve guidelines for hand washing practices & the facilities for it in hospitals of India.